2020
DOI: 10.3390/agronomy10122005
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multi-Component Conditioner with Clinoptilolite and Ascophyllum nodosum Extract for Improving Soil Properties and Zea mays L. Growth and Yield

Abstract: The application of various conditioners in agriculture is one of the management practices used to improve soil quality and plant growth and development. The aim of this study was to assess the effect of a multi-component conditioner on the selected soil properties and maize (Zea mays L.) growth and yield. The effect of a conditioner on a set of soil properties and maize growth and yield was studied in one-year experiments carried out at three study sites, which were under a conventional tillage system. All of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…Additionally, in one study, it was demonstrated that components of commercial A. nodosum extracts influence the quantity and localization of auxins, which may account, at least in part, for the improved plant growth in Arabidopsis seedlings with a DR5:GUS reporter gene construct [ 58 ]. Similar results have been reported with Gracilaria edulis sap in potato [ 59 ], in hybrid maize [ 60 ], in foxtail millet [ 61 ], with Ascophyllum nodosum in maize [ 62 ], in Vigna aconitifolia (Jacq.) Marechal [ 63 ] and in winter wheat [ 64 ] and many more.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, in one study, it was demonstrated that components of commercial A. nodosum extracts influence the quantity and localization of auxins, which may account, at least in part, for the improved plant growth in Arabidopsis seedlings with a DR5:GUS reporter gene construct [ 58 ]. Similar results have been reported with Gracilaria edulis sap in potato [ 59 ], in hybrid maize [ 60 ], in foxtail millet [ 61 ], with Ascophyllum nodosum in maize [ 62 ], in Vigna aconitifolia (Jacq.) Marechal [ 63 ] and in winter wheat [ 64 ] and many more.…”
Section: Discussionsupporting
confidence: 87%
“…It is found that the increase in the amount of potassium absorbed by different crops keeps along with the increase in the concentration of zinc added as fertilizer, this is attributed to the important role of zinc in activating the processes of photosynthesis and respiration through the activation of enzymes whose effect is reflected on the vital plant processes. This demonstrates with what [28,29,30] Proposed. [32] showed that the reason underlies behind the high exchange capacity of zeolite is due to the distinctive silicate structure of zeolite, which gives it open cavities in the form of channels occupied by water molecules and cations such as potassium, sodium, calcium and other exchangeable cations.…”
Section: Grain Weight (Plant -1 G)supporting
confidence: 84%
“…Seaweed-based extracts were recently employed as sustainable tools to improve abiotic stress tolerance, increase nutrient uptake and grape quality. However, the effects of its application into the soil are not yet fully understood [141]; the effect of these soil applications on secondary metabolism compounds, which are fundamental for the quality of grapes and wine, is still scarcely known. More information is known about the use of this biostimulant by foliar application.…”
Section: Categories Of Pbs Class Description Bibliographymentioning
confidence: 99%